Improved Intranasal Retentivity and Transnasal Absorption Enhancement by PEGylated Poly-l-ornithine - Yusuke Kamiya; Tsutomu Yamaki; Shigehiro Omori; Masaki Uchida; Kazuo Ohtake; Mitsutoshi Kimura; Hiroshi Yamazaki; Hideshi Natsume (MDPI AG, 2018)
We reported that the introduction of polyethylene glycol (PEG) to poly-l-ornithine (PLO), which is an homopolymeric basic amino acid having absorption-enhancement ability, prolonged retention time in an in vitro inclined plate test, probably due to an increase in viscosity caused by PEGylation. The aim of the present study is to investigate whether the introduction of PEG chains to PLO improves intranasal retention and transnasal absorption in vivo. We performed intranasal administration experiments using PLO and PEG-PLO with a model drug, fluorescein isothiocyanate dextran (FD-4), in rats under closed and open systems. In the open system, transition of plasma FD-4 concentration after co-administration with unmodified PLO was low, and the area under the plasma concentration-time curve (AUC) decreased to about 60% of that in the closed system. In contrast, the AUC after co-administration with PEG-PLO in the open system was about 90% of that in the closed system, and the transition of plasma FD-4 concentration and FD-4 absorption profile were similar to those of the closed system. These findings indicate that introducing PEG chains to homopolymeric basic amino acids (HPBAAs) is a very useful method for developing a functional absorption enhancer that can exhibit an efficient in vivo absorption-enhancing effect.